Indução eletromagnética (IEM) para estimar atributos de um argissolo vermelho distrófico - Velandia Valero, Niny Johana (2011)
The aim of this study was to use the technique of electromagnetic induction (IEM) to determine the soil density. The study area was carried outon the Experimental Farm of Iguatemi (FEI), Universidade Estadual de Maringá (UEM). In a red dysthropic argisol the study area was prepared with a sub soiling and disking system (conventional tillage) and subjected to charge through the passing wheels of a tractor. The treatments were: control (0 passes), 1 passes, 2 passes, 4 passes and 8 passes of a wheeled tractor. Samples were harvested and undisturbed soils at depths of 0-0.1 m, 0.1-0.2 m, 0.2-0.3 m, 0.3-0.4 m and 0.4-0.5 m for determination volumetric water content, porosity and density. These sites were investigated with the (IEM) soil conductivity. Reading was performed in horizontal dipole, since the vertical dipole estimates were negative for EC. Correction was made for distribution of the differences found at baseline. The IEM data were little altered by instrumental drift due to temperature variation. The soils had elevated density of 1.60 Mg m-3 to 1.83 Mg m-3. Compaction only had effect on the surface (0-0.10 m). For the depth of 0-0.1 m density and total porosity of soil was different between treatments (P <0.001); To the soil water content there was no difference (P> 0.05). The correlation study shows that the EC measure with the EM-38 has no associations with the physical and chemical properties of soil, limiting him to search for the estimation of density in the area with high levels of sand.